Unsupervised word translation for English-Hindi with different retrieval techniques. (16th February 2022) - Pant, Umesh; Chauhan, Shweta; Pant, Pankaj; Daniel, Philemon
Word translation or incorporation of bilingual dictionaries is an important capability that impacts many multilingual language processing tasks. For translation from one language to another language, we either relied on parallel data or bilingual dictionaries. In this paper, we address this problem and generate best cross-lingual word embedding for English-Hindi language pair. Here, we neither use an aligned document or sentence aligned corpus, nor any bilingual dictionary. We are following the assumption of intra lingual similarity distribution that for the most frequent word the distribution graph is similar between Hindi and English corpus and embeddings are isometric. These cross-lingual words embedding can be used for unsupervised neural machine translation and cross-lingual transfer learning. Different retrieval techniques nearest neighbour, inverted nearest neighbours retrieval, inverted Softmax, and cross-lingual word scaling are performed and compared for the bi-lingual embedding of English-Hindi, which is trained for unsupervised and semi-supervised ways by passing seed dictionary. Bi-lingual word embedding is tested on generated English-Hindi dictionary.